One-step construction of novel Ag3PO4/PbBiO2Br composite with enhanced photocatalytic activity. (17th May 2019) - Xia, Yongmei; He, Zuming; Su, Jiangbin
Abstract: In this work, novel Ag3 PO4 /PbBiO2 Br composites have been successfully prepared by one-step chemical precipitation method. The photocatalytic activity of as-prepared photocatalyst was evaluated by decomposing methyl orange (MO) dye under visible light irradiation. The results showed that the Ag3 PO4 /PbBiO2 Br composites exhibited excellent degradation efficiency for MO compared to pure Ag3 PO4 and PbBiO2 Br. The enhanced photocatalytic activity of the Ag3 PO4 /PbBiO2 Br composites can be ascribed to the effective separation of photo-generated electron-hole pairs. Moreover, based on these experiment results, a reasonable mechanism was also proposed to explain the photocatalytic activity of Ag3 PO4 /PbBiO2 Br composites.